2005
DOI: 10.1111/j.1467-789x.2005.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of psychosocial pre‐treatment predictors of weight control

Abstract: Prompted by the large heterogeneity of individual results in obesity treatment, many studies have attempted to predict weight outcomes from information collected from participants before they start the programme. Identifying significant predictors of weight loss outcomes is central to improving treatments for obesity, as it could help professionals focus efforts on those most likely to benefit, suggest supplementary or alternative treatments for those less likely to succeed, and help in matching individuals to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
367
6
17

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(419 citation statements)
references
References 228 publications
29
367
6
17
Order By: Relevance
“…Consistent with research conducted in the West, greater initial weight loss was the dominant predictor of sustained weight loss (17).…”
Section: Discussionsupporting
confidence: 73%
“…Consistent with research conducted in the West, greater initial weight loss was the dominant predictor of sustained weight loss (17).…”
Section: Discussionsupporting
confidence: 73%
“…This supports the conclusions made in a recent comprehensive review of the correlates of weight loss in treatment populations, in which an autonomous, self-motivated cognitive style was one of the strongest predictors of successful weight management. 32 On the whole, however, there were relatively few strong associations between the variables examined in this study and either BMI or 2-year weight change, as indicated by the large number of nonsignificant findings and the relatively modest effect sizes observed. This was particularly the case with correlates of weight change.…”
Section: Discussionmentioning
confidence: 53%
“…This disequilibrium can arise from an excess in calorie intake and/or a deficit in calorie expenditure (lack of physical activity). However, obesity is recognised as a heterogeneous condition and it is accepted that large individual differences in people's ability to control their body weight exist (Schifter & Ajzen, 1985;Teixeira, Going, Sardinha, & Lohman, 2005). Individual differences in behaviours closely related to energy balance or weight control, determine the development of overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%